2021
DOI: 10.3389/fpubh.2021.666442
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Loss of Taste and Smell and Consequent Psychological Effects: A Cross-Sectional Study on Healthcare Workers Who Contracted the COVID-19 Infection

Abstract: The aim of this study was to investigate the correlation between psychological distress and taste and sense of smell dysfunctions on healthcare workers (HCW) who contracted the COVID-19 infection in the midst of the disease outbreak. Reports of sudden loss of taste and smell which persist even after recovery from COVID-19 infection are increasingly recognized as critical symptoms for COVID-19 infections. Therefore, we conducted a cross-sectional study on COVID-19 HCW (N = 104) who adhered to respond to a phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
2
26
0
2
Order By: Relevance
“…Therefore, the long-term persistence (i.e., six months after clinical onset) of such symptoms deserves to be assessed and investigated. Additionally, considering the large number of people affected by COVID-19 worldwide and the negative impact of anosmia and ageusia on the quality of life [ 31 , 40 43 ], it is important to quantify the extent and duration of these symptoms to develop effective interventions able to manage the disorders in subjects with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the long-term persistence (i.e., six months after clinical onset) of such symptoms deserves to be assessed and investigated. Additionally, considering the large number of people affected by COVID-19 worldwide and the negative impact of anosmia and ageusia on the quality of life [ 31 , 40 43 ], it is important to quantify the extent and duration of these symptoms to develop effective interventions able to manage the disorders in subjects with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may not receive adequate medical attention despite their impact on quality of life, especially if prolonged over months. However, olfactory and gustatory deprivations of various cause have been documented as disruptive on daily activities already before the spread of SARS-CoV-2 [ 31 , 40 ], and their negative impact has been recently confirmed by properly designed studies [ 41 43 ]. It is apparent that COVID-19 patients with loss of smell and taste experience a reduced quality of life related to those situations or functions in which the chemical senses play a significant role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the patients receiving the BAs (Inflawell ® group) showed improvement in the clinical symptoms including olfactory and gustatory dysfunction, shortness of breath, cough, body pain and headache. Recent studies have indicated a correlation between the loss of olfactory and gustatory senses with an increase in the feeling of loneliness, depression and anxiety in COVID-19 patients (Kooper 2021 ; Dudine et al 2021 ). Therefore, a faster relief from these symptoms could positively impact patients’ quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine storm contributes to multi-organ damage, and potentially can lead to death of the infected person [46,47]. In many people the viral infection can be asymptomatic, or the virus just causes u-like symptoms such as fever, headache, nausea, and the absence of taste and/or smell [48][49][50][51][52][53][54][55][56]. One of the symptoms that is important in terms of the pathophysiology is the shortness of breath which is essentially due to the extensive cell death since the virus destroys the lining of the lungs that eventually leads to further in ammatory changes in the lung causing improper alveoli function [57].…”
Section: Introductionmentioning
confidence: 99%